LAMAN WORD PRESS SEBAGAI MEDIA BELAJAR DALAM KEGIATAN EKSTRAKURIKULER MENULIS DI ERA DIGITAL - Wina Saputra, Ardi (Widya Warta, 2019)
Digitalization has entered all lines of life. One of them is education. The purpose of this study was to determine the benefits of wordpress pages as a medium for learning extracurricular activities in the digital age. The method used in this research was literature study. The results of this study were to find out the benefits of the wordpress page in terms of elements, types, features, and all other devices. This research can be used as a recommendation for educators to use wordpress pages as learning media and extracurricular activities.